Sustainable freight transport - McKinnon, Alan (Henry Stewart Talks, 2010)
Environmental effects of freight transport, Five key ratios that determine the relationship between economic output and the environmental impact of freight movement, Freight transport intensity: ways of decoupling freight traffic growth from economic growth, Modal split: opportunities for switching freight to 'greener' transport modes, Vehicle utilisation: constraints on vehicle loading and how they can be relaxed, Fuel efficiency: cutting fuel consumption in trucks, ships and planes, Emission intensity: tightening emission standards, electrification of freight transport and use of biofuels